Pengaruh Implementasi Kebijakan Moneter Syariah Terhadap Pertumbuhan Ekonomi di Indonesia Periode 2020-2023 - Octaviana Dainy; Ismatul Hasanah; Siti Sopia; Rasidah Novita Sari (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
The aim of this research is to examine how Indonesia's economic growth in the 2020–2023 era is influenced by the implementation of sharia monetary policy, especially the Bank Indonesia Sharia Certificate (SBIS) and sharia sukuk instruments. This research uses a literature review methodology and analyzes secondary data from sources such as books, scientific journals and articles. An important component of this research is statistical data, which includes information regarding inflation, economic developments and sharia monetary policy collected from official organizations such as the Financial Services Authority (OJK), Bank Indonesia and the Central Statistics Agency (BPS). Economic development and changes in SBIS rates are not significantly correlated, according to data analysis. However, the evolution of Islamic sukuk shows a very encouraging pattern. Investor interest in sharia sukuk is increasing, this shows the enormous potential of this instrument in spurring economic expansion. The findings of this research indicate that sharia sukuk have enormous potential as a source of development financing and can play an important role in driving progress in the Indonesian economy, although the contribution of SBIS is less significant.